Cognitive control and dishonesty. Issue 9 (September 2022) - Speer, Sebastian P.H.; Smidts, Ale; Boksem, Maarten A.S.
Abstract : Dishonesty is ubiquitous and imposes substantial financial and social burdens on society. Intuitively, dishonesty results from a failure of willpower to control selfish behavior. However, recent research suggests that the role of cognitive control in dishonesty is more complex. We review evidence that cognitive control is not needed to be honest or dishonest per se, but that it depends on individual differences in what we call one's 'moral default': for those who are prone to dishonesty, cognitive control indeed aids in being honest, but for those who are already generally honest, cognitive control may help them cheat to occasionally profit from small acts of dishonesty. Thus, the role of cognitive control in (dis)honesty is to override the moral default. Highlights: The precise role of cognitive control in dishonesty has been debated for many years, but now important strides have been made to resolve this debate. Recently developed paradigms that allow for investigating dishonesty on the level of the choice rather than on the level of the individual have substantially improved our understanding of the adaptive role of cognitive control in (dis)honesty. These new paradigms revealed that the role of cognitive control differs across people: for cheaters, it helps them to sometimes be honest, while for those who are generally honest, it allows them to cheat on occasion. Thus, cognitive control is not required for (dis)honesty per se but is required to override one's moral default to be either honest or to cheat. Individual differences in moral default are driven by balancing motivation for reward and upholding a moral self-image.